The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/term.3039
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructed human skin shows epidermal invagination towards integrated neopapillae indicating early hair follicle formation in vitro

Abstract: Application of reconstructed human Skin (RhS) is a promising approach for the treatment of extensive wounds and for drug efficacy and safety testing. However, incorporating appendages, such as hair follicles, into RhS still remains a challenge. The hair follicle plays a critical role in thermal regulation, dispersion of sweat and sebum, sensory and tactile functions, skin regeneration, and repigmentation. The aim of this study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 47 publications
1
43
1
Order By: Relevance
“…2 c). Vimentin is an extracellular matrix component secreted by DP cells while cytokeratin 15 (K15) is an epithelial stem-cell marker 13 , 14 . The cell aggregate containing HUVECs was designated as vHFG.…”
Section: Resultsmentioning
confidence: 99%
“…2 c). Vimentin is an extracellular matrix component secreted by DP cells while cytokeratin 15 (K15) is an epithelial stem-cell marker 13 , 14 . The cell aggregate containing HUVECs was designated as vHFG.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, melanocytes and epidermal cells mixed with the neopapillae to eventually form hair-containing microfollicles with all relevant cell types and structures (Figure 9; Lindner et al, 2011). Additionally, a recent study with neopapillae incorporated in a human full skin equivalent showed an epithelial downgrowth of keratinocytes toward DP spheres and differentiation toward an IRS precursor (Vahav et al, 2020).…”
Section: In Vitro and In Vivo Bioengineered Germs Using Different Cell Populationsmentioning
confidence: 93%
“…Because the main ECM component in the skin is collagen, most studies that track the development of neopapillae employ collagen I scaffolds (Abaci et al, 2018;Lalley and Boyce, 2019;Vahav et al, 2020). When rodent LGR6-positive keratinocytes are loaded in collagen I scaffolds, the keratinocytes are capable of inducing epithelization, hair growth, and angiogenesis in full-thickness wounds (Lough et al, 2016).…”
Section: In Vitro Requirement Of Ecm Proteins For Hf Neogenesismentioning
confidence: 99%
“…LbL-DPC aggregation is akin to that of primary DPCs and has the capacity to restore HF induction potential in vitro and regenerate HFs in vivo. 97 Other biomaterials that contribute to the restoration of HF-inducive ability include human placenta ECM hydrogel, 98 synthesized ECM 99 and a chitosan/polyvinyl alcohol nanofibre sponge with an open-cell cellular structure, 100 which expands the biomaterial libraries for the optimization of the culture environment in vitro to restore the ability of DPCs to regenerate HFs. 3D printing technology for HF regeneration by recapitulating the physiological 3D organization of cells in the HF microenvironment is an innovative biomimetic approach.…”
Section: In Vivo Strategies For Functional Regeneration Of Hfsmentioning
confidence: 99%